"Doing" healthcare at end-of-life: Identity tensions, negotiations, and conflicts. Issue 9 (21st October 2022) - Thompson, Amber; Shura, Isha; Utz, Rebecca
Abstract: Observing how healthcare providers deal with death and dying, in terms of " doing " identity, allows us to explore how they cope with patient end-of-life (EOL) and highlights how the professional identity breaks down while managing patient death and dying. We conducted a digital ethnography of a publicly-accessible online forum for healthcare professionals. Providers' personal experiences with patient death and dying were interpreted through internalized values associated with their professional identity, which when dealing with EOL are challenged and must be negotiated. Training and support are needed to better equip providers with the skills and tools needed at EOL.